Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1128/jvi.80.8.3957-3965.2006
|View full text |Cite
|
Sign up to set email alerts
|

The CPSF30 Binding Site on the NS1A Protein of Influenza A Virus Is a Potential Antiviral Target

Abstract: . Here, we determine whether influenza A virus replication can be selectively inhibited by blocking the ability of its NS1A protein to inhibit the 3-end processing of cellular pre-mRNAs, including beta interferon (IFN-␤) pre-mRNA. Pre-mRNA processing is inhibited via the binding of the NS1A protein to the cellular CPSF30 protein, and mutational inactivation of this NS1A binding site causes severe attenuation of the virus. We demonstrate that binding of CPSF30 is mediated by two of its zinc fingers, F2F3, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
192
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(201 citation statements)
references
References 20 publications
(38 reference statements)
9
192
0
Order By: Relevance
“…The high variability of these residues clearly demonstrates that this interaction is not universal for all influenza A viruses, but is restricted to avian influenza viruses, as reported previously (Heikkinen et al, 2008). The NS1 protein has been implicated in the inhibition of mRNA maturation via interaction with PABPII (Chen et al, 1999) and CPSF30 (Twu et al, 2006). There is no significant conservation among the PABPII interacting residues reported (218-232).…”
Section: Drug Target Sites Of Influenza Ns Proteinsmentioning
confidence: 66%
See 1 more Smart Citation
“…The high variability of these residues clearly demonstrates that this interaction is not universal for all influenza A viruses, but is restricted to avian influenza viruses, as reported previously (Heikkinen et al, 2008). The NS1 protein has been implicated in the inhibition of mRNA maturation via interaction with PABPII (Chen et al, 1999) and CPSF30 (Twu et al, 2006). There is no significant conservation among the PABPII interacting residues reported (218-232).…”
Section: Drug Target Sites Of Influenza Ns Proteinsmentioning
confidence: 66%
“…The highest-ranking binding site (site 1 reported by Q-SiteFinder) is surrounded by the highly conserved residues Trp102, Met104, Asp120, Arg148, Gly158 and Glu159, some of which are in the region that interacts with translation initiation factor eIF4F (see above). This site could form a target for small molecule inhibitors of protein-protein interactions (Twu et al, 2006). Binding sites 2 and 6 are located between highly conserved residues on the RBD, such as Arg19, Arg35 and Arg46.…”
Section: Drug Target Sites Of Influenza Ns Proteinsmentioning
confidence: 99%
“…In contrast, it has been definitively established that the NS1A protein effectively inhibits the production of IFN-␤ mRNA by another mechanism: it binds CPSF30, thereby inhibiting the production of mature cellular mRNAs, including IFN-␤ mRNA (6,7,13). Recombinant viruses that express an NS1A protein containing a mutated binding site for CPSF30 are highly attenuated and induce the production of a substantially increased amount of IFN-␤ mRNA (7,27). In addition, we have shown that this NS1A-binding site is a potential target for the development of antivirals, because blocking the access of CPSF30 for this NS1A site results in increased production of IFN-␤ mRNA and the inhibition of virus replication (27).…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant viruses that express an NS1A protein containing a mutated binding site for CPSF30 are highly attenuated and induce the production of a substantially increased amount of IFN-␤ mRNA (7,27). In addition, we have shown that this NS1A-binding site is a potential target for the development of antivirals, because blocking the access of CPSF30 for this NS1A site results in increased production of IFN-␤ mRNA and the inhibition of virus replication (27). Because inhibition of IFN-␤ mRNA production occurs in the nucleus of influenza A virus-infected cells, a failure of the NS1A protein to enter the nucleus would be expected to result in substantially increased production of IFN-␤ mRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation